Undifferentiated pleomorphic sarcoma of the lateral thigh with KRAS/NF1 co-mutation recurred after repetitive surgical resection: A case report and review of the literature - Zhang, Shuo; Zhou, Zimo; Xu, Jing (Frontiers in Surgery, 2022)
Undifferentiated pleomorphic sarcoma (UPS), as one of a rare soft tissue sarcoma subtype, mainly occurs in the deep parts of the limbs and trunk, showing as rapidly growing painless lumps, rarely located under the skin or protrudes from the skin surface. The risk of recurrence and metastasis is associated with multiple factors. Mutation of tumor gene, tumor occurrence, location and depth of invasion and tumor size have great influence on prognosis. In this study, we described a case of UPS with KRAS/NF1 co-mutation. This case had undergone UPS extended resection for four times, combined with chemotherapy in another hospital. The resection area was more than 3cm, and tumor relapsed after all times operations. This time, tumor protruded from the surface of left lateral with ulceration and infection. Due to multiple surgeries, the anatomy of the lateral femoral vessels has been seriously damaged. We performed expanded tumor resection and adjacent flap transfer repair, meanwhile, VSD negative pressure closed drainage, the patient recovered well after surgery. After surgery, this case was transferred to the department of Oncology for chemotherapy. There was no recurrence after 6 months follow-up. Gene mutation plays an important role in UPS recurrence and metastasis. At the same time, occurrence and location, depth and size of UPS have great influence on the prognosis. Deeper exploration and expanded resection are important for the prognosis of UPS.